2009
DOI: 10.1186/1757-1626-2-9292
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiectomy in post-traumatic suppurative constrictive pericarditis: case report

Abstract: A 13-year-old male was seen at the Hospital with a 5-months history of right chest swelling, pain and recurrent fever and breathlessness on mild exertion. There was a history of gunshot to his chest two and half years before presentation.On admission he was febrile with a temperature of 39°C. The chest wall swelling measuring 6 cm/6 cm was tender and fluctuant and needle aspiration yielded purulent fluids. His blood pressure and pulse were 110/60 mmHg (14.6/8 Kpa) and 100 per minute respectively. The chest rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…All patients require adequate peripheral access and standard ASA monitoring prior to any anaesthetic agent being administered [12,21,22,32,49,[51][52][53][54]. It may also be necessary to institute invasive monitoring via arterial and central venous lines when appropriate, ensuring that insertion of the lines does not delay definitive treatment.…”
Section: Anaesthetic Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…All patients require adequate peripheral access and standard ASA monitoring prior to any anaesthetic agent being administered [12,21,22,32,49,[51][52][53][54]. It may also be necessary to institute invasive monitoring via arterial and central venous lines when appropriate, ensuring that insertion of the lines does not delay definitive treatment.…”
Section: Anaesthetic Techniquesmentioning
confidence: 99%
“…Pericardiectomy is the only definitive treatment for established constriction, and most studies suggest that resection should be as complete as technically feasible [49,[54][55][56][57]. A retrospective review by Nozohoor et al showed that radical pericardiectomy was associated with improved functional status and 10-year survival rates of 94% compared to 55% with subtotal pericardiectomy [55].…”
Section: Pericardiectomy For Constrictive Pericarditismentioning
confidence: 99%
See 3 more Smart Citations